Hypocalcemia in Children Presenting with Afebrile Seizures - Iram Naz, Hafiz Muhammad Muaaz Naeem, Sundas Ikram, Marina Naz, Muhammad Usman, Abdul Rehman, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To record frequency of hypocalcemia in children presenting with afebrile seizures. Methodology: This research includes 333 cases presenting with afebrile seizure for evlaution of hypocalcemia at Ghurki Trust Teaching Hospital Lahore during the year 2018. Each child was investigated for serum calcium. Specimen was collected from antecubital fossa by clean venipuncture using sterile disposable syringe. It was immediately transferred to a clean container with cap and sent to laboratory for analysis. Results: Age range in this study was from 2 months to 7 years with mean age of 3.627±1.68 years, mean duration of seizure 12.864±4.69 hours and mean weight was 16.099±4.44 Kg, 68.2% patients were of male gender and 31.8% patients were females. Conclusion: Hypocalcemia is a key etiological component in afebrile seizures in infants and children. Keywords: Children, afebrilze seizure, hypocalcemia